2018
DOI: 10.3390/math6120327
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric Radial Basis Function Method for Simulation of Elliptic Partial Differential Equations

Abstract: In this paper, the symmetric radial basis function method is utilized for the numerical solution of two- and three-dimensional elliptic PDEs. Numerical results are obtained by using a set of uniform or random points. Numerical tests are accomplished to demonstrate the efficacy and accuracy of the method on both regular and irregular domains. Furthermore, the proposed method is tested for the solution of elliptic PDE in the case of various frequencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…The numerical results of RBF-based algorithms have demonstrated that they are truly meshless, accurate, and easy to implement. Some interesting models can be found in [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The numerical results of RBF-based algorithms have demonstrated that they are truly meshless, accurate, and easy to implement. Some interesting models can be found in [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The numerical results of RBFs based algorithms have demonstrated that it is truly meshfree, accurate and east to implement. Some interesting models can be found in [30,[33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…The horizon of meshless methods is continuously expanding and their applicability is increasing rapidly due to their ease of implementation in higher dimensions on a set of uniform or scattered data points in regular and irregular geometries. In the last few years, it is observed that meshless methods have been extensively employed for numerical simulations of different types of PDEs [29,[42][43][44]. Meshless methods reduce complexity caused due to dimensionality to a large extent which is being faced in the carrying out of conventional methods like finite-element and finite-difference procedures.…”
Section: Introductionmentioning
confidence: 99%